The causality among e-money, manufacturing, services and money supply: an empirical evidence of ASEAN countries - Heryadi Heryadi; Azwardi Azwardi; Sukanto Sukanto (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
The economic transition happened in ASEAN countries caused the increased growth of e-money use. This study was established to discover the causal relation between the growth in manufacturing and service sector and the e-money usage through causality panel approach. Furthermore, this study also focused on finding the causality among the economic growth in manufacturing and service sector, e-money and money supply during 2008-2018 period in the region. The result of the study showed that: (1) there was a one-way causality between the growth in service sector and e-money use, (2) there was no causality between e-money use and the growth in manufacturing sector (3) the growth of money supply provided causal effect on the increase of e-money use.